Biomonitoring and Inter-Annual Variation of Soil Mite (Acari) Diversity and Community Structure in Lamto Guinean Savannah (Co´te d'Ivoire) Submitted to Different Fire Regimes - N'dri, K. Julien; Dosso, Kanvaly; N'Dri, Aya B.; N'Da, Rodolphe Arnaud G.; Kone, Mouhamadou; N'Golo, A. Kone; Fabrice, A. Seka; Pacome, K. Pokou (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
The objective of the study conducted in the Lamto Guinean savannah situated at 165 km northwest of Abidjan, Cote d'Ivoire consisted to assess the changes in soil mite abundance, diversity and community structure specific to the second fire cycle applied in 2015, as well as the inter-annual variation between the two fire cycles (2014 and 2015). Three study sites (Salty marigot, Plateau and North piste) were selected in shrub savannah, where on each, three adjacent stands of 100 m x 50 m formerly delimited were considered. The three fire regimes (early, mid-season, and late fire) were respectively applied on the three sites and stands. Thus, 135 soil cores (5 soil cores x 3 sampling periods x 3 fire regimes or stands x 3 sites) were used for mite extraction. 108 soil cores were taken at two upper layers (0-5 and 5-10 cm) for determination of the bulk density and water content. Whatever the fire regimes, the mean density of soil mites decreased after the fire application. The highest value of density was observed through the early fire (1,715 ± 327 ind.m-2) whereas the lowest value was recorded during the mid season fire (1,433 ± 153 ind.m-2). 41 species had been recorded along the three fire regimes and distributed as follows: early fire 34 species, mid season fire 20 species, and late fire 13 species. The mean species richness of soil mites changed significantly across the fire regimes, and reduced after the fire application, except for the mid season fire. The Simpson diversity index was significantly modified across the fire regimes, and increased after the fire application. Beyond to 24 specialist species, over 50% of the species observed before the burns were rediscovery after the fire application, and could explain this variation. The inter-annual variation of soil mites showed that the density (early fire, mid season fire, and late fire), mite richness (early fire), and diversity (early fire and late fire) increased whereas the mite richness (mid season fire and late fire), and diversity (mid season fire) decreased, respectively, during 2015-burn compared to the previous cycle (2014-burn). The rebound of soil mite parameters during the second fire cycle could be assigned (i) to litter and woody debris, which burn in a mosaic, reflecting local fire intensity, (ii) improving of stand complexity and canopy structure, and (iii) fire tolerance of mites.